Connection Study Motivation of Adolescents Who Have Broken Home with Students' Learning Achievements in Junior High School in Class VII Students of State 1 Perbaungan Academic Year 2021/2022 - Sandra Falisa Hasibuan; Ika Sandra Dewi (International Journal of Educational Research Excellence (IJERE), 2022)
The research method used is descriptive quantitative approach with the type of research used is descriptive correlational research. Determination of the sample of this study is population research because the sample is less than 100. The level of learning motivation of adolescents who experience a broken home is 96.93% in the high category, the level of student learning achievement is 83.57% in the high category, the level of the relationship between adolescent learning motivation which multiplies broken home with student learning achievement is 0.331> 0.284. This shows that there is a relationship between adolescent learning motivation who multiplies broken home and student learning achievement. Based on the discussion and data analysis, it can be concluded that the hypothesis which states "there is a positive and significant relationship between the relationship between adolescent learning motivation who multiplies broken home and student achievement” can be accepted. Where, the higher the relationship of adolescent learning motivation who multiplies broken home with student learning achievement. This shows that there is a relationship between adolescent learning motivation who multiplies broken home and student learning achievement. Based on the discussion and data analysis, it can be concluded that the hypothesis which states "there is a positive and significant relationship between the relationship between adolescent learning motivation who multiplies broken home and student achievement in students class VII SMP Negeri 1 Perbaungan” can be accepted. Where, the higher the relationship of adolescent learning motivation who multiplies broken home with student learning achievement.